2019
DOI: 10.1142/s0192415x19500095
|View full text |Cite
|
Sign up to set email alerts
|

Total Glycosides of Peony Protects Against Inflammatory Bowel Disease by Regulating IL-23/IL-17 Axis and Th17/Treg Balance

Abstract: Inflammatory bowel disease (IBD) is a group of autoimmune diseases, including ulcerative colitis and Crohn’s disease, characterized by nonspecific inflammation in the gut. Total glycoside of peony (TGP) has been widely used for treatment of autoimmune diseases because of its pharmacological effects. However, it is lack of depth in whether TGP regulate T helper 17 cell (Th17) / T regulatory cell (Treg) immune balance or interleukin 23 (IL-23) / IL-17 axis to achieve the goal of treating IBD. Hence, the aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…It is generally believed that the pathogenesis of UC involves the results of multiple interactions including genetics, microorganisms, and the body's immune system [20]. In recent years, the pathogenesis of UC has been continuously studied through UC patients and animal models of UC, and it has been found that the occurrence and development of UC are closely related to the balance of Foxp3 + Tregs cells and Th17 cells (producing IL-17A and IL-17F)in vivo [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally believed that the pathogenesis of UC involves the results of multiple interactions including genetics, microorganisms, and the body's immune system [20]. In recent years, the pathogenesis of UC has been continuously studied through UC patients and animal models of UC, and it has been found that the occurrence and development of UC are closely related to the balance of Foxp3 + Tregs cells and Th17 cells (producing IL-17A and IL-17F)in vivo [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…participate in the pathogenesis of UC by regulating the release of inhibitory cytokines (IL-10, etc. ), and their low number or dysfunction can lead to the occurrence of the disease [23][24][25]. T helper cell 17(Th17) is a subset of T cells capable of secreting IL-17.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In addition, IL-23/IL-23R polymorphisms are involved in pathogenesis of CAD by regulating the immune system. 24 A previous study showed that the IL-23/IL-17 inflammatory signal could adjust the balance of Th17/Treg cells, 25 a process which was related to the progression of CAD. 26 Moreover, the IL-23 level was suggested to be a marker of patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the membranes were incubated with HRP-conjugated goat anti rabbit secondary antibody (1:10000) for 1 h at room temperature. At last, images were obtained from multifunctional Gel Imaging System (Image Quant LAS 500, General Electric, Fairfield, CT, USA), and the gray value of each band was quantified and analyzed using IQTL 8.1 software [23].…”
Section: Protein Extraction and Western Blot Analysismentioning
confidence: 99%